KETERGANTUNGAN DAN KERENTANAN MASYARAKAT TERHADAP SUMBERDAYA DANAU: KASUS DANAU RAWA PENING - . Partomo; Syafri Mangkuprawira; Aida Vitalya S. Hubeis; Luky Adrianto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
Rawa Pening Lake is one kind of ecological systems that played an important social role for its surrounding community. Ecological function of the lake is about to be threaten by many pressure which is natural event as well as anthropogenic occurrence. This may lead to make lake as an ecological system susceptible to external disturbances. This research is intended to identify the degree of community dependency on lake resources and to investigate the extent of vulnerability of surrounding Rawa Pening Lake community. Method employed in this research were descriptive analysis and vulnerability analysis. Research reveals that Kecamatan Tuntang and Ambarawa have high vulnerability, the condition in which the high potential threat may put on the track to the destruction of lake natural resources and environment. Keywords: dependency, vulnerability, lake.